1 and 2 Timothy, Titus - Fee, Gordon D.; Gasque, W. Ward. (Peabody, MA : Hendrickson Publishers, 1988)
The present edition of this commentary has been totally reset and rewritten to comment on the text of the New International Version (NIV). Nonetheless, it is still substantially the same as the original Good News Commentary, first published in 1984. These three letters (1 and 2 Timothy and Titus), called the Pastoral Epistles (PE) since the eighteenth century, purport to be letters from the Apostle Paul to two of his younger co-workers, whom he has left in charge of the churches in Ephesus and Crete, respectively. Since the early nineteenth century, however, when doubt was first expressed by F. Schleiermacher, a large array of arguments has been forthcoming that have called their authenticity into question, so that at present the large majority of NT (New Testament) scholars worldwide consider them not authored by Paul but by a pseudepigrapher (although a disciple of Paul), around the turn of the first century A.D. The present commentary has been written from the perspective of Pauline authorship, fully aware of the many difficulties that entails but convinced that theories of pseudepigraphy have even greater historical difficulties. - Introduction.
1 Timothy -- Titus -- 2 Timothy.
"Revised edition"--Pref.
Includes bibliographical references (p. [305]-313) and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries